The British booksellers: a novel of the Forgotten Blitz (Thomas Nelson, 2024)
"Based on real accounts of Britain's Land Girls and the Forgotten Blitz, The British Booksellers highlights the courageous choices we must make to live, love, and - in the face of all that tests us - fight for what matters most"--

Where rivers part: a story of my mother's life (Atria Books, Simon & Schuster, 2024)
"In the 1960s when Kalia's mother, Chue, was born, the US was actively recruiting Hmong Laotians to assist with CIA efforts in Laos's Secret War. By the time Chue was a teenager, the US had completely vacated Laos, and the country erupted into genocidal attacks on the Hmong people, who were perceived as traitorous for their involvement. Notably, from 1964-1973, Laos became victim to the heaviest bombardment by the United States against communist Pathet Lao, becoming the most heavily bombed country in history. Fearing vengeful soldiers looking to take their lives, Chue and her family quickly fled their village for the jungle, leaving all that they knew behind. Perpetually on the run, the family was often on the brink of starvation, and death loomed. During this tumultuous period, Chue met her husband, Bee, and unwittingly left her mother behind forever when she escaped to a refugee camp with his family, a mistake she would regret for the rest of her life. There, Chue, Bee, and their daughters lived in a state of constant fear and hunger until they finally made it to America. The determined couple enrolled in high school classes despite being in their late twenties and worked grueling factory jobs to provide for their family, yet most who meet Chue know nothing of her extraordinary resilience and traumatic past. In Where Rivers Part, told from her mother's point of view, Kao Kalia Yang unveils her mother's epic struggle towards safety and the important undocumented history of a time and place most US readers know nothing about, offering insight into America's Secret War in Laos with tenderness and unvarnished clarity. In doing so, she excavates the plight of many refugees, who suffer silently and are often overlooked as one of the essential foundations of this country. For readers of The Wild Swans by Jung Chang, The Spirit Catches You When You Fall Down by Anne Fadiman, and those who flock to stories about survival during wartime, Where Rivers Part is not only a personal account of resilience and survival but also a powerful and transporting look into Laos's Secret War and the lived experiences of the Hmong people"--
Part I: Try to imagine , Part II: If you woke up one morning , Part III: Heaven and Earth are shaken , Part IV: Return of the refugee

Skies of thunder: the deadly World War II mission over the roof of the world (Viking, 2024)
"In April 1942, the Imperial Japanese Army steamrolled through Burma, capturing the only ground route from India to China. Supplies to this critical zone would now have to come from India by air-meaning across the Himalayas, on the most hazardous air route in the world. SKIES OF THUNDER is a story of an epic human endeavor, in which Allied troops faced the monumental challenge of operating from airfields hacked from the jungle, and took on "the Hump," the fearsome mountain barrier that defined the air route.They flew fickle, untested aircraft through monsoons and enemy fire, at brain-melting altitudes with inaccurate maps and only primitive navigation technology. The result was a litany of both deadly crashes and astonishing feats of survival. The most chaotic of all the war's arenas, the China-Burma-India theater was further confused by the conflicting political interests of Roosevelt, Churchill and their demanding, nominal ally, Chiang Kai-shek. Caroline Alexander, who wrote the defining books on Shackleton's Endurance and Bligh's Bounty, is brilliant at probing what it takes to survive extreme circumstances. She has unearthed obscure memoirs and long-ignored records to give us the pilots' and soldiers' eye views of flying and combat, as well as honest portraits of commanders like the celebrated "Vinegar Joe" Stillwell and Claire Lee Chennault. She assesses the real contributions of units like the Flying Tigers, Merrill's Marauders, and the British Chindits, who pioneered new and unconventional forms of warfare. Decisions in this theater exposed the fault-lines between the Allies-America and Britain, Britain and India, and ultimately and most fatefully between America and China, as FDR pressed to help the Chinese nationalists in order to forge a bond with China after the war. A masterpiece of modern war history"--
The Burma Road , The air , The hump , The valley of death , Night flight , Number One Air Commando , The Ledo Road , End of the road

Fifty-three days on Starvation Island: the World War II battle that saved Marine Corps aviation (Hachette Books, 2024)
"On August 20, 1942, twelve Marine dive-bombers and nineteen Marine fighters landed at Guadalcanal. Their mission: defeat the Japanese navy and prevent it from sending more men and supplies to "Starvation Island," as Guadalcanal was nicknamed. The Japanese were turning the remote, jungle-covered mountain in the south Solomon Islands into an air base from which they could attack the supply lines between the U.S. and Australia. The night after the Marines landed and captured the partially completed airfield, the Imperial Navy launched a surprise night attack on the Allied fleet offshore, resulting in the worst defeat the U.S. Navy suffered in the 20th century, which prompted the abandonment of the Marines on Guadalcanal. The Marines dug in, and waited for help, as those thirty-one pilots and twelve gunners flew against the Japanese, shooting down eighty-three planes in less than two months, while the dive bombers, carried out over thirty attacks on the Japanese fleet. Fifty-Three Days on Starvation Island follows Major John L. Smith, a magnetic leader who became America's top fighter ace for the time; Captain Marian Carl, the Marine Corps' first ace, and one of the few survivors of his squadron at the Battle of Midway. He would be shot down and forced to make his way back to base through twenty-five miles of Japanese-held jungle. And Major Richard Mangrum, the lawyer-turned-dive-bomber commander whose inexperienced men wrought havoc on the Japanese Navy. New York Times bestselling author John R. Bruning depicts the desperate effort to stop the Japanese long enough for America to muster reinforcements and turn the tide at Guadalcanal. Not just the story of an incredible stand on a distant jungle island, Fifty-Three Days on Starvation Island also explores the consequences of victory to the men who secured it at a time when America had been at war for less than a year and its public had yet to fully understand what that meant. The home front they returned to after their jungle ordeal was a surreal montage of football games, nightclubs, fine dining with America's elites, and inside looks at dysfunctional defense industries more interested in fleecing the government than properly equipping the military. Bruning tells the story of how one battle reshaped the Marine Corps and propelled its veterans into the highest positions of power just in time to lead the service into a new war in Southeast Asia"--